Challenges and success factors of female entrepreneurs: evidence from a developing country - Mustapha, Mazlina; Subramaniam, Punitha (Econjournals, 2016)
Entrepreneurship is claimed as an important element to stimulate growth and development of most countries. It is also posited that female entrepreneurs took part and played a vital role in the economic development and helped to stabilize the economy particularly during the economic recession periods. Thus, this paper attempts to explore the success factors of women entrepreneurs in Malaysia, one of the developing countries in Asia. In addition, it also examines the challenges faced by these women in conducting their businesses. Interviews were conducted with ten successful female entrepreneurs. The interview results appear to indicate that support from family members is important and contribute to the sustainability of their businesses. In addition, their internal motivation and creativity help them to attract the customers and compete in the market. This study provides information to the regulators and government agencies about the training, support and financial resources needed by this group of entrepreneurs.